(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Wide-ranging usages of nanomaterials have become physiologically safe as a result of the global focus on studying green nanotechnology. The creation of nanoparticles with a regular shape and set of characteristics is the focus of nanotechnology. According to recent research in the field of nanotechnology, the size, shape, composition, level of crystallinity, and stability of metal nanoparticles are all factors that affect how they behave. Due to their great biocompatibility, stability, and relatively low toxicity, bimetallic nanoparticles are essential. Bimetallic nanostructures on graphene, zeolites, clays, fibers, and polymers, as well as non-supported bimetallic nanoparticles, are reviewed. Their production processes, resultant characteristics, and antibacterial activity are all presented. The ratio of the two metals in a bimetallic nanoparticle population as well as the internal distribution of the elements inside specific nanoparticles (such as the presence of homogeneous alloys, core-shell systems, and potential intermediary phases) are the two main elements that make up this population. Biological applications (in medicine and agriculture), environmental applications (in water treatment and removal of toxic contaminants), engineering applications (in Nano sensors, nanochips, and nano-emicon- ductors), and chemical and physical applications (in optics, catalysis, and paints) are just a few of the many uses they have thanks to their synergistic properties.